Ekologi yang Integral dalam Terang Interpretasi Kitab Suci - Antonius Obe Haryon (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2022)
The natural wealth contained in this universe was created by God and given to humans to be guarded and preserved. God gives “freedom” to humans to work on all that is in this nature. The Bible emphasizes how the earth was created by God for humans to be used properly. Harmony between humans and nature, is a meeting point for mutual respect. Therefore, an attitude of respect for nature is very much needed in order to maintain this harmony. God as the Creator and Organizer of all things, therefore there is not a single being that escapes His sight. God always gives a clear direction and purpose for all that He has created, so that the creatures do not fight for each other's places and get rid of each other, but with the uniqueness that exists in each of them, will coloring this life and Worship the God who has organized everything. The loving God seeks to care for what He has created, He keeps in His loving arms, He embraces even the lowliest in the eyes of human.